Bridging Innovation and Emissions Reduction: How Energy Public R&D Investments Shape Decarbonization Across Economic Divides - Nugroho Nugroho (Green Publisher Indonesia, 2025)
This research investigates how public research investments in energy affect greenhouse gas emission reductions across nations with varying income levels. The OLS regression analysis shows a significant negative correlation, indicating that increased public funding for clean energy innovation leads to decarbonization. GDP and population size remain the main factors driving emissions despite research efforts, illustrating the challenging task of achieving both economic growth and sustainability. Propensity Score Matching (PSM) helped mitigate selection bias and solidify the causal connection between R&D investments and emissions reductions. Despite their leadership in R&D investment, high-income countries maintain elevated per capita emissions, demonstrating that technological innovation must be supported by additional policies, including carbon pricing and regulatory measures. Lower-income nations face substantial financial obstacles to clean energy development, highlighting the necessity for global partnerships, along with technology sharing and international financial support models.